HIV-1 Infection of Human Thymic Stromal Cells and Thymocytes In Vitro - Tomasz Rozmyslowicz; Dareus O. Conover; Glen N. Gaulton (HIV/AIDS Research and Treatment-Open Journal, 2015)
We studied in vitro Human Immunodeficiency Virus type 1 (HIV-1) infection within human thymic cell cultures as a model to explain the consequences of HIV-1 on the thymic microenvironment. Although HIV-1 inIfection may exert direct thymic cytopathicity, the majority of thymocytes remain uninfected. One hypothesis to explain this effect is that infection of stromal cells, including tissue macrophages, within the thymic microenvironment alters the normal cross-talk between stromal cells and thymocytes thereby disrupting thymocyte maturation. Accordingly, to establish a role for the thymic pathogenicity of HIV-1 we investigated the in vitro susceptibility of thymocytes and Thymic Macrophages (TM) to infection with a series of lab adapted HIV-1 that display well defined patterns of tropism: Ba-L(R5), HXB2(X4), and 89.6(R5/X4). We found that thymocytes were most productive in supporting the replication of the R5/X4-tropic virus 89.6 early in culture and displayed more significant replication of the X4-tropic virus HXB2 only after 7-14 days of culture. Replication of the R5 topic virus Ba-L was not detected. In contrast, although HIV-1 replication was delayed overall in cultures of thymic stromal cells enriched for TM, by day 7-21 these cultures supported the replication of both the R5/X4 tropic virus 89.6 and the R5-tropic virus Ba-L, but only transiently HXB2. Thus, while both thymic stromal cells and thymocytes are capable of supporting HIV-1 replication, they display markedly different patterns of susceptibility linked to HIV-1 tropism. Given the exquisite sensitivity of thymocyte development and selection on stromal cell function these results point to new mechanisms for HIV-1 infection in disrupting the maturation of thymocytes.